Home (Office) is where your Heart is - Julian Marx; Stefan Stieglitz; Felix Brünker; Milad Mirbabaie (Business & Information Systems Engineering, 2023)
Working conditions of knowledge workers have been subject to rapid change recently. Digital nomadism is no longer a phenomenon that relates only to entrepreneurs, freelancers, and gig workers. Corporate employees, too, have begun to uncouple their work from stationary (home) offices and 9-to-5 schedules. However, pursuing a permanent job in a corporate environment is still subject to fundamentally different values than postulated by the original notion of digital nomadism. Therefore, this paper explores the work identity of what is referred to as 'corporate nomads'. By drawing on identity theory and the results of semi-structured interviews, the paper proposes a conceptualization of the corporate nomad archetype and presents nine salient identity issues of corporate nomads (e.g., holding multiple contradictory identities, the flexibility paradox, or collaboration constraints). By introducing the 'corporate nomad' archetype to the Information Systems literature, this article helps to rethink established conceptions of "home office" and socio-spatial configurations of knowledge work.
Keywords: 000; Corporate nomadism; Identity theory; Home office; Knowledge work; Digital nomadism